The Visible Invisibles: Visual Representation of Servants and Slaves from Feudalism to Capitalism (KULT_online, 2024)
Diane Wolfthal analyzes the visualization of slaves and domestic servants in visual media. Domestic servants found their way into commissioned works or entered as subject into the discourse of the ruling elite. Wolfthal surveys the period from 1300 to 1700 to show the social change from feudalism to capitalism, which is reflected in a globalized servanthood marked by a changing understanding of roles from lifelong service to profession.